A heterostakeholder cooperation for sustainable internet policymaking - Luca Belli (Internet Policy Review, 2015)
The article discusses the rise of a multistakeholder approach to internet policymaking and takes a critical stance with regard to the sole reliance on the multiplicity of stakeholders rather than focusing on the heterogeneity of stakeholders' interests. The article analyses the evolution of the multistakeholder discourse from the Tunis Agenda for the Information Society to the NETmundial Multistakeholder Statement. Secondly, it presents a selection of examples of stakeholder inclusion within policy-development processes at national and international level. Thirdly, it argues that the focus on the diversity of stakeholders' interests, rather than the mere affiliation with different stakeholder groups, may provide a more suitable conceptual framework for the elaboration of sustainable policies. As a conclusion, an embryonic model of heterostakeholder approach is put forward. Such an approach may be used to assess the diversity of interests represented within internet governance processes and strengthen pluralism of ideas and interests.
Keywords: 300; Heterostakeholder; Multistakeholder; Internet policymaking; Internet governance